2002
DOI: 10.1128/aem.68.4.2093a-2093a.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Water Potential and Temperature Stresses on Cryptosporidium parvum Oocysts

Abstract: Page 5465, column 2, lines 8 to 13: "2,4-dihydroxylamino-6-nitrotoluene; the para substituent is then reduced to form 4-amino-2-hydroxylamino-6-nitrotoluene. The 4-amino-2-hydroxylamino-6-nitrotoluene is subsequently transformed to a compound tentatively identified as 2-amino-5-hydroxy-4-hydroxylamino-6-nitrotoluene" should read "2,4-dihydroxylamino-6-nitrotoluene. The 2-hydroxylamino group rearranges to yield a compound tentatively identified as 2-amino-5-hydroxy-4-hydroxylamino-6-nitrotoluene."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…It is important, therefore, when modelling the fate of pathogens in the environment, that inactivation rates used are appropriate for temperatures for the climate in question. Previous studies have examined inactivation of Cryptosporidium at temperatures of up to 30°C (Walker et al. 2001; Jenkins et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important, therefore, when modelling the fate of pathogens in the environment, that inactivation rates used are appropriate for temperatures for the climate in question. Previous studies have examined inactivation of Cryptosporidium at temperatures of up to 30°C (Walker et al. 2001; Jenkins et al.…”
Section: Discussionmentioning
confidence: 99%
“…Salt solutions ( ca 250 ml) containing 0·08 and 0·77 mol −1 NaCl were placed into the bottom of sealable airtight jars (capacity ca 2 l). According to the literature, these molal NaCl solutions produce and maintain simulated soil matric potentials of approximate field capacity and dry conditions respectively (wilting point) (Walker et al. 2001), and were designated ‘wet’ and ‘dry’ in this study.…”
Section: Preparation Of Soil Microcosmsmentioning
confidence: 99%
“…Interestingly,this earlier study found a sixfold higher prevalence of C. parvum in fecal samples collected per rectum from the adult cattle (1.1%) compared with the very low prevalence of C. parvum (0.18%) in fecal pats collected off the ground from the same herds on the same day. This suggests that once fecal material is deposited in the environment, C. parvum oocysts are subjected to one or more environmental stressors (e.g., thermal) that function to reduce the effective environmental load of this protozoal parasite (Walker et al, 2001). For example, we have shown that seasonal temperature fluctuations common to California's agricultural regions induce rapid inactivation via premature excystation of C. parvum oocysts once the daily maximum air temperature exceeds 25°C (Li et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…[64] We assume that the biological decay rate of oocysts is 3.48 Â 10 À6 hr À1 [Robertson et al, 1992] regardless of whether microorganisms are attached to soil particles or not. This rate could be modified with further information about temperature and soil moisture content prior to storm events [Walker et al, 2001]. Hence k di , i = 1, .…”
Section: Parameter Estimation From Experimental Datamentioning
confidence: 99%